Revitalization of heritage buildings after disasters (the roofed market in the city of Homs in Syria is a model): إحياء المباني التراثية بعد الكوارث ( السوق المسقوف في مدينة حمص في سورية أنموذجاًﹰ ) - Nour Mtanios Abboud, Tariq Hossam El Din, Abdel Masih Ashi (Journal of engineering sciences and information technology, 2018)
Disasters cause damage at all economic، social and cultural levels، and perhaps physical and architectural damage is the living recording of wars. And cause extensive destruction of property and life، especially the destruction of architecture and architecture associated with the community، which represents the memory and identity of this group. In partitular the destruction of traditional architecture، which includes a variety of buildings depicting different types of buildings، and all kinds of thesea bUildings are a special nature that dictates a special methis in dwaking with them and depends on the importanice of the buildings and it’s histoptical value and the possibilities available. The architectural buildings are of a different nature from the other modern buildings. The architect who built them no longer exists، to explain to us his traditional ways of building. The modern buildings are still well-built and can be consulted at any time for any repairs or modifications. To reflect on the revival of heritage-value buildings that have been hit by disasters In this regard، the aim of this research is to consider how to reconstruct heritage buildings that have been destroyed and destroyed by wars and disastersv as a symbolic value that must be preserved، as well as theoretical concepts related to architectural heritage to architextural heritage، esamples and how to apply the trend on the roofed market in the city of homs in Syria.